The relationship between self-harm and bullying behaviour: results from a population based study of adolescents - Ingri Myklestad; Melanie Straiton (BMC, 2021)
Abstract Background This study aims to better understand the association between bullying behaviour (the bullied, the bullies and the bully-victims) and self-harm, and which protective factors moderate this association. Methods A total of 16,182 adolescents, aged 12 to 19 years, were invited to participate in the cross-sectional Ung-data survey. This survey covered various aspects of young people's lives. The response rate was 87%. To assess the relationship between self-harm and bulling behaviour, and psychological- and environmental covariates, we conducted logistic regression analyses. In addition, we tested for potential interaction effects between protective factors and the three bullying groups on self-harm. Results Fifteen percent of participating adolescents reported engaging in self-harm during the last year. The risk of self-harm was six times higher for the "bully-victims", five times higher for the bullied, and three times higher for the bullies, compared to the "neither-bullied nor bullies". The risk of self-harm in the face of being bullied was significantly greater for girls than boys. Depression, anxiety and parental conflict accounted for some of the association between being bullied and self-harm, and between bully-victims and self-harm. School behavioural problems accounted for some of the association between the bullies and self-harm and the bully-victims and self-harm. The relationship between the bullied and self-harm was significantly moderated by parental support and school well-being, while the relationship between "bully-victims" and self-harm was moderated by school well-being. Conclusion There is a strong link between bullying and self-harm. Interventions to address bullying may reduce self-harm. Our findings also suggest that high levels of parental support and school well-being may buffer the harmful relationship between bullying behaviour and self-harm. Addressing these factors may be important in reducing the risk of self-harm among those experiencing bullying.